Is There a Relationship Between Serum Levels of Vitamin A, Vitamin E, Copper and Zinc and Otitis Media with Effusion in Children? - Aydogan, Filiz (Springer India, 2012)
The aim of this study is to determine whether the serum levels of vitamin A, vitamin E, copper and zinc have a role in the development of otitis media with effusion (OME) in childhood. This prospective study was conducted between February 2010 and February 2011 at a tertiary Otorhinolaryngoloy Clinic. There were 113 subjects and subdivided into three groups. Group 1 consisted of 44 patients who underwent adenoidectomy with ventilation tube placement due to OME. Group 2 consisted of 43 patients underwent adenoidectomy alone and group 3,called control group, included 26 healthy children. Serum values of vitamin A, vitamin E, copper and zinc were measured preoperatively. Comparison of the patient groups showed that group 1 patients had significantly lower serum zinc levels than group 2 patients (p = 0.002), although differences between both patients groups and controls were not significant. We found that the differences among the three groups in terms of serum levels of vitamin A, vitamin E and copper were not statistically significant (p > 0.05). The results of this study showed that serum levels of vitamin A, vitamin E and copper may not play a role on development of OME. We postulated that high serum zinc status may have the preventive effect in the predisposition to OME which may related to adenoid hyperplasia.